Understanding of Teaching and its Manifestation Among Excellent Educators in a Selected Public University - Abdullah, Hasnah (2005)
The research was conducted to explore the understanding of teaching of excellent educators at a selected public university. Three research questions guided the study; first, what do educators believe to be the purpose of education?, second, what facilitated the understanding of teaching development?, and third, how is the understanding of teaching adhered to, manifested in their teaching practice? The study employed qualitative multiple case study approach to answer the research questions. The primary data were collected through in depth interviews and the secondary data were collected through observations in the classroom,laboratory and discussion sessions after lectures. The analysis of this study were done through within-case analysis and cross-case analysis. The within-case analysis explained in detail the finding from excellent educators which were carried out individually. Meanwhile, the cross-case analysis explained the findings generally from the four excellent educators. The study discovered that the purposes of education according to the excellent educators were for change, transmitting of knowledge, and character building. Change in this context was seen with reference to the individual and societal development. It becomes the responsibility for a person who holds the knowledge to, then transmit and thus share the knowledge with others - to students directly or indirectly. The knowledge transmitted must be congruent with the behaviour of the transmitter. Education was seen as a means to shape positive behaviour. Respondents' backgrounds as well as understanding of learning and teaching concepts had contributed to the development of their understanding of teaching. The learning concept was to boost knowledge and appropriate application of the obtained knowledge. The teaching concepts discovered were to transmit knowledge. Teaching was also seen as a means for them to change students' paradigm towards knowledge and its uses. However, the conceptions of learning and teaching towards adult students were slightly different. Learning was seen as a means to understand and make meaning of the new and previous knowledge while teaching was seen as a means to transmit knowledge and to increase students' knowledge. The purpose of education, respondents' background and learning and teaching conceptions have shaped their understanding of teaching. The adhered understanding of teaching was manifested in their teaching. These can be observed through their preparation and openness to assist students. Their teaching roles as experts and organizers were reflected in their teaching. They have been a major source of reference for their students as well as the society at large. The study recommended that comparisons between other institutes of learning be made with the end result of reaping the best from every quarter. This concept should be expanded to others, other than the educators, that is, to include managers, politician and the world at large.